Non-equilibrium critical point in Be-doped low-temperature-grown GaAs - Mohamed, Mohd Ambri; Pham, Tien Lam; N., Otsuka (American Institute of Physics, 2013)
We studied the transition process of antisite arsenic defects in Be-doped low-temperature-grown GaAs layers by measuring the magnetization. This material exhibits bistability at non-equilibrium; at a ﬁxed temperature in a ﬁxed magnetic ﬁeld a sample relaxes towards two different states, depending on the preceding cooling process. We observed anomalously large magnetization ﬂuctuations in macroscopic samples during the transition from bistability to monostability with gradual change of the temperature. Slowing down of the relaxation of the magnetization is observed as a sample approaches the transition into monostability. Large ﬂuctuations observed from a two-piece sample exhibit intermittent bursts by high-pass ﬁltering and follow a generalized Gumbel probability density distribution. These observations suggest a possibility of the occurrence of a non-equilibrium critical point in this material. Microscopic processes underlying the observed phenomena are discussed with results of ﬁrst-principles calculations of strain ﬁelds. VC 2013 American Institute of Physics.